In Search of the Holy Grail - Kinga Blaschke; Zuzanna Łazarewicz; Anna Sieroń (Grafica: Documents de Disseny Gràfic)
This essay explores the search for an ideal typography course for design students. It analyzes the historical and social context of typography in post-war Poland, highlighting the impact of a non-democratic state on graphic design. It addresses the legacy of elitist education and linguistic uniformity, revealing challenges in the current education system. An interdisciplinary team seeks to define the ideal course through qualitative and quantitative research, underlining the need to understand the history of typography and its current challenges. Models of design education are discussed, recognizing the absence of a perfect course and focusing on the need to define clear frameworks, standardize content and include modern media in typography education.